MODELING AND FORECASTING SUSTAINABLE ECONOMIC DEVELOPMENT OF AGRIBUSINESS ENTITIES (Conference Zone, 2022)
This article econometrically models the sustainable economic development of agribusiness entities, in particular, farms, which are its leading link, and predicts sustainable development in the future.